Association of citrus psorosis B symptoms with a sequence variant of the Citrus psorosis virus RNA 2 - Velázquez, Karelia; Pina, José A.; Navarro, Luis; Moreno, Pedro; Guerri, José (2017)
Citrus psorosis virus (CPsV), the type species of genus Ophiovirus, is the presumed causal agent of a bark scaling disease in citrus plants. CPsV virions are kinked filaments composed of three negative-strand RNA molecules and a similar to 48-kDa coat protein. The virus induces two different syndromes: psorosis A (PsA), characterized by limited bark scaling lesions in the trunk and main limbs, and a more aggressive form of the disease called psorosis B (PsB) with rampant bark lesions affecting even thin branches and chlorotic blotches in old leaves. In the greenhouse, the PsA and PsB syndromes can be induced by graft inoculating healthy citrus seedlings with non-lesion or with lesion bark inoculum from PsA-affected field trees. PsA- and PsB-inducing CPsV sub-isolates obtained by this procedure from the same tree showed identical single-strand conformation polymorphism (SSCP) profiles in homologous segments of the RNAs 1 and 3, whereas segments of the RNA 2 enabled discrimination between PsA- and PsB-associated sequence variants. SSCP analysis of the RNA 2 population present in different tissues of psorosis-infected plants showed that: (i) PsA-inducing isolates contain PsB-associated sequence variants at low frequency, (ii) the PsB-associated sequence variant is predominant in blistered twigs and gummy pustules affecting old leaves, characteristic of PsB isolates, and (iii) the PsB-associated sequence variant accumulates preferentially in bark lesions of the trunk and limbs. SSCP analysis of the RNA 2 population also enabled monitoring of interference between PsA- and PsB-associated variants in plants co-inoculated with both psorosis types.